Papéis ocupacionais e pessoas com deficiências físicas: independência, tecnologia assistiva e poder aquisitivo - Cruz, Daniel Marinho Cezar da (2012)
The aim was to investigate if there is association between occupational roles, independence, purchasing power, age, time of disability and technology in the lives of people with physical disabilities living in the city of São Carlos, São Paulo, Brazil. For this, we attempted to compare if there was a variation in the number of occupational roles in the three times (past/present/future), according to gender and among two groups (adults and elderly), to describe the performance patterns of occupational roles (absence, continuum, loss, gain); identify which are assistive technology resources that these individuals have and how did the acquisition of these technologies, usability and abandonment; identify the knowledge about the subject of granting policies of technologies. From a cross-sectional research, with a convenience sample, we selected 91 subjects, aged from 18 to 93 years, enrolled in Family Health Care Units, with some physical disability. The sample was divided in two groups: adults (n = 34) and elderly (n = 57) to compare the results between them. The instruments of data collection were the Role Checklist, the Modified Barthel Index, the Brazil Economic Classification Criterion and a form developed by the researcher. For data analysis we used a quantitative approach composed by descriptive analysis, ANOVA with repeated measures and Correspondence Analysis. As an outcomes, we found that the participants showed a considerable repertoire of technologies, mostly acquired with their own funds or donations. Much of these technologies could be granted by the grant program of the Federal Government, however, the list of technologies identified in this study suggests that these individuals also make use, as well as other technologies require not covered by the grant program. It was observed a trend toward reliance on subject, and this trend follows a higher order of dependence to total independence. For assistive technology, it was observed that the classes with smaller number of technology classes were related to independent and in greater numbers, with some dependency classes. With regard to the purchasing power it was noted that the classes C1 and D were more associated with less dependence, since the classes B1, B2 and C2 to a moderate dependence and class A2, besides with low frequency and little explanation, coupled with a reliance on more high. It should be noted that although the technology was not directly associated with the independence, the latter was associated with a greater number of occupational roles, which requires a look at the issues of independence, when considering the typology of occupational roles and how this independence moves between roles in the daily life of these participants. From the data obtained, some implications are done in order to increase actions developed in the health care of people with disabilities and the improvement of public policies for this population.